Genetic dissection of cassava brown streak disease in a genomic selection population - Nandudu, Leah; Kawuki, Robert; Ogbonna, Alex; Kanaabi, Michael; Jannink, Jean-Luc (Frontiers in Plant Science, 2023)
Cassava brown streak disease (CBSD) is a significant threat to food security in East and central Africa. Breeding for resistance against CBSD is the most economical and sustainable way of addressing this challenge. This study seeks to assess the (1) performance of CBSD incidence and severity; (2) identify genomic regions associated with CBSD traits and (3) candidate genes in the regions of interest, in the Cycle 2 population of the National Crops Resources Research Institute. A total of 302 diverse clones were screened, revealing that CBSD incidence across growing seasons was 44%. The severity scores for foliar and root symptoms ranged from 1.28 to 1.99 and 1.75 to 2.28 across seasons. Broad sense heritability ranged from low to high (0.15 - 0.96), while narrow sense heritability ranged from low to moderate (0.03 - 0.61). Five QTLs, explaining approximately 19% phenotypic variation was identified for CBSD severity at 3 months after planting on chromosomes 1, 13, and 18 in the univariate GWAS analysis. Multivariate GWAS analysis identified 17 QTLs that were consistent with the univariate analysis including additional QTLs on chromosome 6. Seventy-seven genes were identified in these regions with functions such as catalytic activity, ATP-dependent activity, binding, response to stimulus, translation regulator activity, and transporter activity among others. These results suggest variation in virulence in the C2 population, largely due to genetics and annotated genes in these QTL regions may play critical roles in virus initiation and replication, thus increasing susceptibility to CBSD.